THEORETICAL RESEARCH ON VIBROACOUSTIC DYNAMICS UNDER BALL-AND-ROD HARDENING OF BAR- AND PLANE-TYPE PARTS - Andrey N. Leshchenko; Anatoly P. Babichev (Advanced Engineering Research, 2012)
The theoretical research on the noise emission process under the ball - and - rod hardening of the bar - and plane - type parts is considered. The analytic dependences of the produced noise spectra are obtained. That is th e basis for making the engineering de cisions on the bringing the acoustic characteristics to the sanitary norms at the design stage of such processes.